2007
DOI: 10.1086/517616
|View full text |Cite
|
Sign up to set email alerts
|

Hypomorphic Mutations in the Gene Encoding a Key Fanconi Anemia Protein, FANCD2, Sustain a Significant Group of FA-D2 Patients with Severe Phenotype

Abstract: FANCD2 is an evolutionarily conserved Fanconi anemia (FA) gene that plays a key role in DNA double-strand-type damage responses. Using complementation assays and immunoblotting, a consortium of American and European groups assigned 29 patients with FA from 23 families and 4 additional unrelated patients to complementation group FA-D2. This amounts to 3%-6% of FA-affected patients registered in various data sets. Malformations are frequent in FA-D2 patients, and hematological manifestations appear earlier and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
119
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 116 publications
(129 citation statements)
references
References 57 publications
(98 reference statements)
6
119
1
3
Order By: Relevance
“…2 In humans, FANCD2 could be essential for embryonic survival, considering that all the FANCD2 mutations identified in human patients are hypomorphic. 24 The fact that Fancc Ϫ/Ϫ mice have a normal-sized KSL stem and progenitor pool could imply that nonubiquitinated Fancd2 has indispensable roles in these developmental processes, as some have recently speculated. 2 An important finding of this study is that Fancd2 Ϫ/Ϫ mice have a compromised marrow environment that is less supportive for stem cell population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In humans, FANCD2 could be essential for embryonic survival, considering that all the FANCD2 mutations identified in human patients are hypomorphic. 24 The fact that Fancc Ϫ/Ϫ mice have a normal-sized KSL stem and progenitor pool could imply that nonubiquitinated Fancd2 has indispensable roles in these developmental processes, as some have recently speculated. 2 An important finding of this study is that Fancd2 Ϫ/Ϫ mice have a compromised marrow environment that is less supportive for stem cell population.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Interestingly, there is some evidence that patients with FANCD2 mutations have earlier onset and more rapid progression of hematologic manifestations. 24 It is also noteworthy that all the FANCD2 mutations identified in human patients are hypomorphic, whereas Fancd2 Ϫ/Ϫ mice have null mutations. 21,24 We therefore hypothesized that Fancd2 Ϫ/Ϫ mice might have more severe hematopoietic defects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 However, more recently it has been reported that this complementation group accounts for approximately 6% of all FA patients. 20 Patients belonging to the FA-D2 complementation group display the common FA congenital malformations including skin hypo-or hyper-pigmentation, short stature, and microcephaly ( Table 1). [20][21][22] Importantly, these physical abnormalities, along with skeletal irregularities such as radial ray deformities, often allow for early clinical diagnosis.…”
Section: Fancimentioning
confidence: 99%
“…Currently, 15 genes related to FA have been identified [2][3][4], and to date, limited phenotype/genotype correlations have been determined with the exception of cancer incidence in Group D1 [5][6][7].…”
mentioning
confidence: 99%